Pendidikan Kampus Sebagai Media Penanaman Nilai-nilai Antikorupsi Bagi Mahasiswa - Asep Syarifuddin Hidayat (SALAM: Jurnal Sosial dan Budaya Syar-i, 2019)
Abstract.Corruption has been happening for a long time in Indonesia. The practice of abuse of authority, bribery, giving facilitation payments, illegal fees, giving rewards on the basis of collusion and nepotism as well as the use of state money for personal interests, are interpreted as acts of corruption and are considered as common things in this country. Ironically, nowadays there is a lot of corruption that occurs not only among officials but also in small communities. Although efforts to eradicate it have been carried out for more than four decades, however, these corrupt practices continue, there is even a tendency for the modus operandi to be more sophisticated and organized, making it even more difficult to overcome.Keywords: Anti-corruption Education, KPK, Community Culture Abstrak.Korupsi telah terjadi sejak lama di Indonesia. Praktik penyalahgunaan wewenang, penyuapan, pemberian uang pelicin, pungutan liar, pemberian imbalan atas dasar kolusi dan nepotisme serta penggunaan uang negara untuk kepentingan pribadi, oleh masyarakat diartikan sebagai suatu perbuatan korupsi dan dianggap sebagai hal yang lazim terjadi di negara ini. Ironisnya, saat ini banyak korupsi yang terjadi bukan hanya pada kalangan pejabat saja tetapi pada kalangan masyarakat kecil. Walaupun usaha-usaha pemberantasannya sudah dilakukan lebih dari empat dekade, namun, praktik-praktik korupsi tersebut tetap berlangsung, bahkan ada kecenderungan modus operandinya lebih canggih dan terorganisir, sehingga makin mempersulit penanggulangannya.Kata Kunci: Pendidikan Antikorupsi, KPK, Budaya Masyarakat